On Some Properties of Generalized Inverse Hyperbolic Functions - Nantomah, Kwara; Kasimu, Osman (Asia Pacific journal of mathematics, 2020)
In this paper, we provide inverses for some generalized hyperbolic functions. We also study some properties of these inverse functions. Furthermore, by using basic techniques, we establish some inequalities (or bounds) for the inverse functions. As a by-product of the established results, we obtain some inequalities (or bounds) for the logarithmic function.